Respuestas

  • Usuario de Brainly
2013-10-31T21:16:42+01:00
Solución:
Sabemos que f(x)= x^2 y (fog)(x)= 4x^2 - 12x  + 9
De esta última se factoriza así:

=> 4x^2 - 12x + 9 = [(4x)^2 - 12(4x) + 36] / 4

..........................= [ (4x - 6) (4x - 6) ] / 2x2

..........................= [ 2 (2x - 3) 2(2x - 3) ] / 2x2 .......(samplificando el dos)

..........................= (2x - 3) (2x - 3)
..........................= (2x - 3) ^2
Luego g(x) = 2x - 3 => Respuesta.

Espero haberte colaborado. Suerte.